2022
DOI: 10.15567/mljekarstvo.2022.0204
|View full text |Cite
|
Sign up to set email alerts
|

Th1 / Th2 cytokine polarization in milk according to different pathogens causing subclinical mastitis in cows

Abstract: The aim of this study to determine the Th1/Th2 cytokine balance in milk according to the bacterial species that cause subclinical mastitis in cows. The California Mastitis Test (CMT) was applied to the selected cows. The cows were divided into four groups: cows with negative CMT (n = 45); Escherichia coli (E. coli) group included only cows with E. coli growing in CMT-positive milk samples (n = 45); Streptococcus agalactiae (S. agalactiae) group included cows with only S. agalactiae growing in CMT-positive milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Unlike the study by Hisae-da et al (2001), in the present study, it was observed that as the SCC levels increased, the concentration of milk TNF-α and IFN decreased, while the concentration of IL-5 increased. The TNF-α concentration was higher in the Escherichia coli (E. coli) group than in the Staphylococcus aureus (S. aureus) and the Streptococcus agalactiae (S. agalactiae) groups (Safak et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Unlike the study by Hisae-da et al (2001), in the present study, it was observed that as the SCC levels increased, the concentration of milk TNF-α and IFN decreased, while the concentration of IL-5 increased. The TNF-α concentration was higher in the Escherichia coli (E. coli) group than in the Staphylococcus aureus (S. aureus) and the Streptococcus agalactiae (S. agalactiae) groups (Safak et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Somatic cell count was measured in raw milk samples using a DeLaval Cell Counter® (Cellcounter DCC; DeLaval, Sweden) device and in accordance with the manufacturer's manual and methods in the literature (Safak et al, 2022). As stated in the previous study (Safak and Risvanli, 2022), the raw milk samples with different SCC (˂ 150,000, 151,000-400,000, 401,000-600,000, 601,000-1,000,000, and >1,000,000 cells⁄mL) were determined.…”
Section: Methodsmentioning
confidence: 99%